2017
DOI: 10.3390/su9101787
|View full text |Cite
|
Sign up to set email alerts
|

Developing Policy Scenarios for Sustainable Urban Growth Management: A Delphi Approach

Abstract: In many parts of the world, a rapid urbanization process is taking place at an unprecedented scale, and its drastic impacts on societies and the environment are evident. To combat the externalities of such rapid, and to a degree uncontrolled, development, many cities around the globe introduced various urban growth management policies. However, policy making-to provide sustainable outcomes, while generating growth opportunities-has been a daunting task for urban administrators. To ease the task, scenario-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 122 publications
0
79
0
3
Order By: Relevance
“…The method was first developed by RAND Corporation in the 1960s to explore ideas and seek consensus among a panel of experts [35,36]. Nowadays, the method is widely used in a variety of sectors, such as nursing studies [37]; marketing [38]; tourism [39]; urban studies [40]; and education [41]. Given the exploratory nature of this study, using the Delphi method was an appropriate way to address the research goals.…”
Section: Methodsmentioning
confidence: 99%
“…The method was first developed by RAND Corporation in the 1960s to explore ideas and seek consensus among a panel of experts [35,36]. Nowadays, the method is widely used in a variety of sectors, such as nursing studies [37]; marketing [38]; tourism [39]; urban studies [40]; and education [41]. Given the exploratory nature of this study, using the Delphi method was an appropriate way to address the research goals.…”
Section: Methodsmentioning
confidence: 99%
“…Discussion and feedback were necessary to address inconsistencies and build a cohesive set of guidance; however, discussion introduces biases that influence decisions in group settings. The Delphi method [60][61][62][63] was selected to facilitate a panel of experts to discuss and prioritize key aspects of collaborative approaches for their application in low-income countries while also reducing group biases by allowing for anonymity over multiple rounds of rating with controlled feedback on panel opinions.…”
Section: Point Of Departure and Research Questionmentioning
confidence: 99%
“…Delphi method had been used in many areas and can be used for any purpose requiring the use of committees [58][59][60][61][62]. Based on many studies, Sourani and Sohail (2015) presented Delphi as useful to (a) obtain accurate information that is unavailable, (b) handle complex problems that require more judgmental analysis, (c) define areas where there is considerable uncertainty and/or a lack of agreed knowledge or disagreement, (d) allow for combining fragmentary perspectives into a collective understanding, (e) model a real-world phenomenon involving a range of viewpoints and for which there is little established quantitative evidence, and (f) highlight topics of concern and assess uncertainty in a quantitative manner [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77].…”
Section: Purposesmentioning
confidence: 99%
“…More recently, Delphi has been widely used to develop the criteria and indicators in many fields, especially in construction fields [56][57][58][59][60][61][62]; for example, Sourani and Sohail (2015) [63] used the Delphi technique to develop an agreed set of economic sustainability criteria that should be addressed in a procumbent strategy. Moreover, many studies [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] have showed that Delphi can be useful to (a) obtain accurate information that is unavailable, (b) handle complex Sustainability 2019, 11, 3166 3 of 32 problems that require more judgmental analysis, (c) define areas where there is considerable uncertainty and/or a lack of agreed knowledge or disagreement, (d) allow for combining fragmentary perspectives into a collective understanding, (e) model a real world phenomena involving a range of viewpoints and for which there is little established quantitative evidence, and (f) highlight topics of concern and assess uncertainty in a quantitative manner. In particular, based on the summary explained in Appendix A [78][79][80][81][82][83][84], this research accordingly chose the Delphi technique to develop sustainable city indicators (SCIs) for Cambodia through three-round panel surveys.…”
mentioning
confidence: 99%